Twenty-five years of palivizumab: a global historic review of its impact on the burden of respiratory syncytial virus disease in children - Carbonell-Estrany, Xavier; Simões, Eric A.F.; Bont, Louis; Manzoni, Paolo; Zar, Heather J.; Greenough, Anne; Ramilo, Octavio; Stein, Renato; Law, Barbara; Mejias, Asuncion; Sanchez, Luna Manuel; Checchia, Paul A.; et al. (Informa UK Limited, 2025)
Introduction: Respiratory syncytial virus (RSV) causes significant morbidity and mortality in young children. For 25 years, palivizumab has been the only effective pharmaceutical RSV preventive.
Areas covered: We summarize the development and a quarter-century of real-world evidence with palivizumab. We highlight its positive impact on the burden of RSV in high-risk children. Based on lessons learnt from its implementation, we suggest strategies for effective and equitable deployment of newer RSV preventives.
Expert opinion: Following failure of the formalin-inactivated RSV vaccine in 1967, RSV intravenous immunoglobulin was approved in 1996 after three decades' research. Subsequently, palivizumab emerged as the most effective and safe RSV preventive, demonstrated by the IMpact trial, and was licensed in 1998 in the United States. Over the last 25 years, the benefits of palivizumab have been firmly established through a wealth of evidence, predominantly from high-income countries (HICs). To achieve a global impact with the newer RSV preventives, evidenced-based universal guidelines must be developed and endorsed by regulatory authorities and relevant scientific societies. Independent economic evaluations should incorporate all RSV-associated healthcare costs, reduction of long-term respiratory sequelae, and standardized outcomes. Most importantly, equity in product availability and implementation, particularly in low- and middle-income countries (LMICs) is essential.